Effect of Cystic Fibrosis Transmembrane Receptor Modulators on Anthropometric and Growth Parameters in Individuals with Cystic Fibrosis: A Systematic Review (OR36-08-19). (13th June 2019) - Alvarez, Jessica; Bailey, Julianna; Bowser, Ellen; Farnham, Kristen; Sr., Mark Mangus,; McDonald, Catherine; Padula, Laura; Porco, Kat; Rozga, Mary
Abstract: Objectives: Individuals with cystic fibrosis (CF) are at high risk for malnutrition and poor growth. New drugs that modulate CF transmembrane receptor (CFTR) function are available, although their effects on anthropometric parameters are not clear. This systematic review aimed to determine if various CFTR modulator therapies affect weight and growth parameters in individuals with CF. Methods: A literature search was conducted using MEDLINE, CINAHL and Embase databases for peer-reviewed, randomized controlled trials (RCT) published from January 2002 to May 2018 that examined the effect of CFTR modulation therapy on weight and growth parameters in children and adults with CF. Articles were screened for relevance, data was extracted and summarized, and risk of bias was assessed to determine the quality of evidence. Results: A total of 612 original articles were identified, and 13 articles representing 10 RCTs were included in qualitative synthesis and three were included in quantitative synthesis. All but one RCT demonstrated low risk of bias. The targeted class of CFTR mutation varied by RCT. Studies indicated that, in children and adults with CF with class III mutations, ivacaftor treatment alone increased weight and BMI (4 RCTs), but it did not influence growth in individuals with class II (1 RCT) or class IV mutations (1 RCT). Treatment with ivacaftor + lumacaftor in adults homozygous for the F508del CFTR mutation (class II) increased BMI following 24 weeks of treatment (2 RCTs), but there was no effect in adults heterozygous for the mutation treated for 8 weeks (1 RCT). Treatment with lumacaftor + tezacaftor in individuals ages 12–20 years with class II mutations did not change growth parameters (1 RCT). Conclusions: Effects of CFTR modulators on increasing weight and growth in individuals with CF are likely dependent on the therapy formulation (single vs combination therapy) and the targeted CFTR mutation. Whereas ivacaftor alone increases weight and growth parameters in individuals with class III mutations, ivacaftor + lumacaftor is more effective at increasing BMI in adults homozygous for the class II F508del CFTR mutation. Additional studies are needed to determine effects of other CFTR modulator drugs on growth parameters in individuals with varying CFTR mutations. Funding Sources: Academy of Nutrition and Dietetics/Medical Nutrition DPG, National Institutes of Health.